What Do They Talk About Translanguaging? Students and Lecturers’ Voices From Legal English Classes - Widya Pertiwi Anwar; Muhammad Basri Jafar; Amirullah Abdullah; Andi Sakinah Ayu Lestari Dirhamzah; Misnawati Misnawati (Universitas Cokroaminoto Palopo, 2025)
This qualitative case study investigated the use and perceptions of translanguaging in English for Law courses within Islamic Law programs at a university in Indonesia. Data were collected through semi-structured interviews with 30 students and 3 English lecturers. The findings reveal that both students and teachers actively engaged in translanguaging, drawing on a repertoire of languages, including English, Indonesian, Bugis (the local language), and Arabic. Translanguaging served multiple pedagogical functions, including facilitating conceptual understanding, promoting inclusivity, and enhancing student engagement. However, the study also highlighted the need for a balanced approach to translanguaging, ensuring adequate exposure to the target language (English) and clear code-switching practices. The implications of these findings for pedagogy, curriculum development, and teacher training are discussed. This study contributes to the growing body of literature on translanguaging in education and provides valuable insights for educators working in multilingual and multicultural contexts